Conditions, Standards and Practices of Inclusion for Children with Disabilities in Italian Infant School - Lucia Chiappetta Cajola (LED Edizioni Universitarie, 2015)
The highly integrative choice that Italy has decided to make for many decades is much appreciated at international level. It is an irreversible choice that requires continual improvements to be made in the school context which includes a great variety of individuals. During childhood, in fact, Italian school embraces, promotes and enriches the experience of every child from a developmental perspective; the educational activities offer opportunities for growth within a context oriented towards well-being, awareness and gradual development of the competences expected at different ages, between three and six years old. In such educational activities, the school is coherent with the principles of the inclusion of the person, considering the acceptance of diversity and active participation in each of the fundamental values. This paper regards the perspective of inclusion of children with disabilities in Italian infant school. It describes, both quantitatively and qualitatively, the situation, according to a framework of fundamental principles sanctioned internationally, based on the Italian Constitution, current laws, documents, informations and data from authoritative sources. The research, presented by the author in the «Deutschen Gesellschaft für Erziehungswissenschaft Kongress» (Humboldt Universität, Berlin, 9-12 March 2014), arose from a designed European comparative study from four selected member countries of the EU: Italy, England, Germany and Slovenia. The study aims to explain how inclusive education of children with disabilities in european school has developed, and how, currently, is arranged in connection with the school system's resources, the teachers training and the social expectations on the kindergarden.